Multiple modifications in cis elements of the long terminal repeat of retroviral vectors lead to increased expression and decreased DNA methylation in embryonic carcinoma cells. - Challita, P M (1995)
Infection by murine retroviruses in embryonic carcinoma (EC) and embryonic stem cells is highly restricted. The transcriptional unit of the Moloney murine leukemic virus (MoMuLV) long terminal repeat (LTR) is inactive in EC and embryonic stem cells in association with increased proviral methylation. In this study, expression in F9 EC cells was achieved from novel retroviral vectors containing three modifications in the MoMuLV-based retroviral vector: presence of the myeloproliferative sarcoma virus LTR, substitution of the primer binding site, and either deletion of a negative control region at the 5' end of the LTR or insertion of a demethylating sequence. We conclude that inhibition of expression from the MoMuLV LTR in EC cells is mediated through the additive effects of multiple cis-acting elements affecting the state of methylation of the provirus.